2013
DOI: 10.1590/s0100-204x2013000800011
|View full text |Cite
|
Sign up to set email alerts
|

Deposição de nutrientes na carcaça de girinos de rã-touro

Abstract: Resumo -O objetivo deste trabalho foi determinar a deposição de nutrientes na carcaça de girinos de rã-touro (Lithobates catesbeianus) por meio de modelo não linear. Foram utilizados 2.700 girinos com peso médio inicial de 0,039 g. Ração comercial farelada com 55% de proteína bruta foi fornecida ad libitum. Os animais foram pesados e avaliados a cada dez dias para análise dos conteúdos de proteína bruta, extrato etéreo, água e sais minerais. Os parâmetros do modelo Gompertz foram estimados pelo método de Gauss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 27 publications
0
5
0
1
Order By: Relevance
“…Usually, these models consist of nonlinear functions and several studies including different mathematical models can be found in the literature. These models are usually applied for the evaluation of the growth kinetics of a wide range of animals, including birds (Aggrey, 2002;Sezer & Tarhan, 2005;Nahashon, Aggrey, Adefope, Amenyenu, & Wright, 2006), mammals (Curi, Nunes, & Curi, 1985;Silva, Alencar, Freitas, Packer, & Mourão, 2011;Franco et al, 2011), fishes (Hernandez-Llamas & Ratkowsky, 2004;Santos, Mareco, & Silva, 2013), reptiles (Bardsley, Ackerman, Bukhari, Deeming, & Ferguson, 1995) and amphibians (Rodrigues et al, 2007;Mansano, Stéfani, Pereira, & Macente, 2013). Some mathematical functions commonly used in these studies include the Gompertz, Logistic, Brody, von Bertalanffy and Richards growth models (France et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Usually, these models consist of nonlinear functions and several studies including different mathematical models can be found in the literature. These models are usually applied for the evaluation of the growth kinetics of a wide range of animals, including birds (Aggrey, 2002;Sezer & Tarhan, 2005;Nahashon, Aggrey, Adefope, Amenyenu, & Wright, 2006), mammals (Curi, Nunes, & Curi, 1985;Silva, Alencar, Freitas, Packer, & Mourão, 2011;Franco et al, 2011), fishes (Hernandez-Llamas & Ratkowsky, 2004;Santos, Mareco, & Silva, 2013), reptiles (Bardsley, Ackerman, Bukhari, Deeming, & Ferguson, 1995) and amphibians (Rodrigues et al, 2007;Mansano, Stéfani, Pereira, & Macente, 2013). Some mathematical functions commonly used in these studies include the Gompertz, Logistic, Brody, von Bertalanffy and Richards growth models (France et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The water (87.29% to 88.83%), protein (6.14% to 7.35%), fat (2.69% to 3.37%), and ash (1.36% to 1.42%) content of tadpoles fed corn and peeled banana, avocado, and pumpkin meal correspond to studies that determined the protein requirement for bullfrog tadpoles (Pinto et al, 2015). Additionally, they correspond to studies that compared the nutrient content between a commercial and an experimental diet for bullfrog tadpoles (Mansano et al, 2014), and research evaluating the nutrient deposition using a commercial fish diet containing 40% crude protein (Mansano et al, 2013). Histological studies of the organs of bullfrog tadpoles have shown that diets formulated for fish can cause organ damage in the tadpoles, even those containing low protein (Seixas Filho et al, 2008a).…”
Section: Discussionmentioning
confidence: 88%
“…Similar results have been described for bullfrog tadpoles fed a diet with 270 g/kg digestible protein, which showed a centesimal composition of 851.5 g/kg moisture, 87.9 g/kg protein, 44.3 g/kg fat, and 15.7 g/kg ash (Pinto et al, 2015). In another study, the same species receiving commercial feed with 550 g/ kg CP showed a centesimal composition of 881.5 g/kg moisture, 70.0 g/kg protein, 36.0 g/kg fat, and 12.4 g/kg ash (Mansano et al 2013). In an experiment using a commercial feed containing 360.00 g/kg CP, bullfrog tadpoles had a body composition consisting of 863.8 g/kg moisture,…”
Section: Discussionmentioning
confidence: 91%